The Influence of School Principal Leadership, Teacher Motivation, and Culture Organization on Teacher Performance Junior High School in Bitung - Sumual, Herry; Sumual, Tinneke E. M.; Theno, Ignatius Rudi; Dondokambey, Rainier N; Liow, Evans S. (International Journal of Information Technology and Education, 2024)
This research aims to determine the influence of the head’s participative leadership style schools, teacher work motivation, and organizational culture on junior high school teacher performance. Study this is ex post facto research. The research population was all-state junior high school teachers in Bitung City. The size sample study Which amounts to 118 Teachers, was chosen based on the proportional sampling technique. It was a drafting instrument made in the form of a questionnaire, with answers on a scale of 1-4, consisting of 54 items. Details of the instruments used to collect data that meet the requirements of construct analysis and status valid. Its reliability is calculated with the technique alpha Cronbach. Analysis data use technique regression simple And regression double For test hypothesis study. Results study prove: (1) there is an influence significant style leadership the principal’s participation in teacher performance, (2) there is a significant influence on teacher work motivation on teacher performance; (3) there is a significant cultural influence on organization to performance Teacher; (4) there is influence Which significant style leadership principal, teacher work motivation, and organizational culture together towards performance Teacher.